2020
DOI: 10.2337/dc20-1444
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes and COVID-19–Related Mortality in the Critical Care Setting: A National Cohort Study in England, March–July 2020

Abstract: To describe the relationship between type 2 diabetes and all-cause mortality among adults with coronavirus disease 2019 (COVID-19) in the critical care setting. RESEARCH DESIGN AND METHODS This was a nationwide retrospective cohort study in people admitted to hospital in England with COVID-19 requiring admission to a high dependency unit (HDU) or intensive care unit (ICU) between 1 March 2020 and 27 July 2020. Cox proportional hazards models were used to estimate 30-day in-hospital all-cause mortality associat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
106
3
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(122 citation statements)
references
References 38 publications
11
106
3
2
Order By: Relevance
“…In Italy, a diabetes prevalence of 17% was reported in patients admitted to intensive care units for severe COVID-19 (16). Recent data confirmed the findings mentioned above, outlining a diabetes prevalence of 18.3% in English people with severe COVID-19 requiring critical care treatment (high dependency unit or intensive care unit) (21). Other study showed a significant prevalence of diabetes (30.05% vs 19.57%) in dead patients compared to survivors in ICU wards in Spain (22).…”
Section: Prevalence Of Diabetes and Its Clinical Severity In Patientssupporting
confidence: 62%
“…In Italy, a diabetes prevalence of 17% was reported in patients admitted to intensive care units for severe COVID-19 (16). Recent data confirmed the findings mentioned above, outlining a diabetes prevalence of 18.3% in English people with severe COVID-19 requiring critical care treatment (high dependency unit or intensive care unit) (21). Other study showed a significant prevalence of diabetes (30.05% vs 19.57%) in dead patients compared to survivors in ICU wards in Spain (22).…”
Section: Prevalence Of Diabetes and Its Clinical Severity In Patientssupporting
confidence: 62%
“…However, these findings could still be relevant to clinically well COVID-19 patients monitored in the community or primary care setting. Third, patients with Types 1 and 2 DM were not differentiated in our study, as both types of diabetes were reported to have an increased risk of adverse COVID-19 outcome, 46,47 and separating them would have further reduced the statistical power of our analysis. Fourth, testing of IL-6 or tumor necrosis factor-α as inflammatory markers were not available for routine use in Singapore as they are not cost-effective compared to CRP.…”
Section: Limitations and Strengthsmentioning
confidence: 99%
“…Meanwhile, a nationwide retrospective cohort study from the UK evaluating COVID-19 Hospitalisation in England Surveillance System (CHESS) found that COVID-19 patients with T2DM hospitalized in the critical setting (high dependency unit (HDU) and ICU were at 23% increased risk all-cause mortality; adjusted hazard ratio (aHR) of 1.23 [95% CI 1.14, 1.32]), which was lower than the aforementioned studies [24]. Importantly, the aHR for the younger age group (age 18-49 years) were significantly higher compared to the older groups ( [25].…”
Section: Diabetes and Poor Outcomes Of Covid-19 Diseasementioning
confidence: 90%